2016
DOI: 10.1016/j.tws.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

The continuous strength method for steel cross-section design at elevated temperatures

Abstract: When subjected to elevated temperatures, steel displays a reduction in both strength and stiffness, its yield plateau vanishes and its response becomes increasingly nonlinear with pronounced strain hardening. For steel sections subjected to compressive stresses, the extent to which strain hardening can be exploited (i.e. the strain at which failure occurs) depends on the susceptibility to local buckling. This is reflected in the European guidance for structural fire design EN1993-1-2 [1], which specifies diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…For materials which exhibit these stress-strain characteristics, it is conventional to use the 0.2% proof strength f 0.2p as the design strength. Beyond this point, no further strain hardening is considered in traditional design, though it is considered, and systematically harnessed, in the deformation based continuous strength method [26][27][28]. The non-linear stress-strain characteristics lead to some differences in the structural performance of stainless steel members compared to carbon steel members, which are generally reflected in the design rules set out in EN 1993-1-4 [29].…”
Section: Fire Resistant Design Of Structural Stainless Steelmentioning
confidence: 99%
“…For materials which exhibit these stress-strain characteristics, it is conventional to use the 0.2% proof strength f 0.2p as the design strength. Beyond this point, no further strain hardening is considered in traditional design, though it is considered, and systematically harnessed, in the deformation based continuous strength method [26][27][28]. The non-linear stress-strain characteristics lead to some differences in the structural performance of stainless steel members compared to carbon steel members, which are generally reflected in the design rules set out in EN 1993-1-4 [29].…”
Section: Fire Resistant Design Of Structural Stainless Steelmentioning
confidence: 99%
“…Local buckling was also reported for column specimens -106 in total, mostly from Rectangular Hollow Sections (RHS) and Square Hollow Sections (SHS) sections-tested under fire conditions as referenced in the paper by Theofanous et al [17]. The majority of these tests were carried out in ETH, Zurich (detailed information about them is given in [18]), with the authors concluding that the reason for the observed local buckling failure was the small magnitude of the global geometric imperfections and the low slenderness values of the columns.…”
Section: Experimental Studies Of Rolled Columnsmentioning
confidence: 95%
“…Fig. 2 shows the local buckling failure of a SHS specimen and a H-section specimen of the programme referenced by Theofanous et al [17]. In other experimental work [19], hot-rolled H-section column stubs were tested under fire exposure with the authors reporting failure due to local buckling at the flanges.…”
Section: Experimental Studies Of Rolled Columnsmentioning
confidence: 99%
See 2 more Smart Citations